OSCILLATORY BEHAVIOR OF SEMI-CANONICAL THIRD-ORDER DELAY DIFFERENTAL EQUATIONS WITH A SUPERLINEAR NEUTRAL TERM - Vidhyaa, K. S.; Deepalakshmi, R.; Graef, John R.; Thandapani, E. (Applicable analysis and discrete mathematics, 2024)
A class of third-order semi-canonical differential equations with a superlinear neutral term of the type ( a ( t ) [ ( b ( t ) ( x ( t ) + p ( t ) x α ( τ ) ) ’ ) ’ ] β ) + q ( t ) x λ ( σ ( t ) ) = 0 is considered. Some oscillation conditions are presented which are new in form and complement those already reported in the literature. Some examples illustrating the main results are provided.